Methods used to adapt FAIR principles to scientific data (Geo-Eco-Marina, 2023)
This paper presents an analysis of the FAIR principles. It is addressed to data managers and scientists (as data producers and users) and aims to point out the crucial importance of providing proper metadata and take all the necessary actions in order for the databases to follow the FAIR principles.
Keywords: FAIR; digital object; research data; data management